2011
DOI: 10.1007/s11102-010-0290-z
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline versus bromocriptine in the treatment of hyperprolactinemia: a systematic review of randomized controlled trials and meta-analysis

Abstract: Cabergoline and bromocriptine are the most used drugs in the treatment of hyperprolactinemia, they are able to normalize the prolactin levels, restore gonadal function and promote tumor reduction in the majority of patients. We undertake a systematic review and meta-analysis of randomized controlled trials to compare cabergoline versus bromocriptine in the treatment of patients with idiopathic hyperprolactinemia and prolactinomas. The data sources were: Embase, Pubmed, Lilacs and Cochrane Central. The outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 26 publications
1
55
0
4
Order By: Relevance
“…These females are overweight, infertile, and anovulatory and have profound alterations in the reproductive endocrine axis (23). In the present study, we found that hyperprolactinemia was essential for the phenotypic defects of the hCGβ+ females because most of them were reversed by treatment with dopamine agonists with proven efficacy in hyperprolactinemia (16, 17, 20, 35). …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These females are overweight, infertile, and anovulatory and have profound alterations in the reproductive endocrine axis (23). In the present study, we found that hyperprolactinemia was essential for the phenotypic defects of the hCGβ+ females because most of them were reversed by treatment with dopamine agonists with proven efficacy in hyperprolactinemia (16, 17, 20, 35). …”
Section: Discussionmentioning
confidence: 53%
“…Of them, bromocriptine has been used over the past 30 yr, but a considerable number of patients are resistant to this treatment, and it has multiple side effects (12, 13). Cabergoline provides an alternative often with better results (1416), and the ovulatory cycle and fertility can be recovered after cabergoline treatment in patients with hyperprolactinemia due to macro- or microprolactinomas (17). In addition, cabergoline administration to female rats prevents embryo implantation due to a deficiency in progesterone production (18).…”
mentioning
confidence: 99%
“…It has been proven that treatment of hyperprolactinaemia in menopausal women improves their bone mineral density (BMD) [61, 62]. The results of the studies were confirmed in the group of men with hyperprolactinaemia [63, 64]. It was noticed that the patients who received dopaminergic agonist drugs obtained an increase in BMD.…”
Section: Hyperprolactinaemia During the Menopausementioning
confidence: 97%
“…A recently published meta-analysis of randomized controlled trials has shown that CBG is more effective in normalizing prolactin levels and is associated with less adverse events when compared to BRC [3]. However, the therapeutic use of high daily doses of CBG has been associated with clinically significant valvular heart disease in patients with Parkinson's disease in a dose-dependent manner [4,5].…”
Section: Introductionmentioning
confidence: 99%